A visit to Centralized Sewage Treatment Plant in UiTM Penang - Chan, Hun Beng; Raja Mohd Noor, Raja Nor Husna; Musir, Adhilla Ainun; Keria, Roziah; Kamarudin, Faizah; Zakariah, Zulfairul (Unit Penerbitan FKAPP, 2025)
The course of Mechanical and Electrical Engineering is offered to Part 3 of Bachelor Degree in Civil Engineering (EC223) students. One of the topics in the course is Wastewater Treatment Process. A visit to the Centralized Sewage Treatment Plant (Loji Kumbahan Terpusat) in UiTM Cawangan Pulau Pinang was carried out with the consent from the Facility Unit to expose our students of the practices. The capacity of the treatment is 10,000 PE. It is gated and locked to avoid trespassing by individual without the proper consent by Facility Unit. According to the facilitator, the first step of the process is Primary Mechanical Screen, which aims to remove physical objects such as papers and plastics to prevent damage and clogging of downstream equipment, piping, and appurtenances.